The Slavcleft: A three-center study of the outcome of treatment of cleft lip and palate. Part 2: Dental arch relationships - Fudalej, Piotr S; Urbanova, Wanda; Klimova, Irena; Dubovska, Ivana; Brudnicki, Andrzej; Polackova, Petra; Kroupova, Daniela; Kotova, Magdalena; Rachwalski, Martin (Journal of cranio-maxillo-facial surgery, 2019)
PURPOSE: Our aim was to evaluate the dental arch relationship in a preadolescent Slavic population with unilateral cleft lip and palate (UCLP) by using the Goslon Yardstick. MATERIALS AND METHODS: Patients treated in Warsaw, Poland (n = 32), Prague, Czech Republic (n = 33) and Bratislava, Slovakia (n = 30) were included in this retrospective study. Each cleft center used a unique surgical protocol. Three raters scored blindly the dental arch relationship on plaster models. Intra- and inter-rater agreement were assessed with kappa statistics, and differences between the groups were evaluated with one-way analysis of variance. Intra-rater agreement was very good (k > 0.825), while inter-rater agreement was either good or very good (kappa >0.703). RESULTS: We found that patients treated in Warsaw showed a more favorable dental arch relationship (Goslon score = 2.58, SD = 0.77) than patients treated in Prague (Goslon score = 3.21, SD = 1.04). Patients treated in Bratislava showed an intermediate Goslon score (3.07; SD = 0.99). CONCLUSION: This study showed that the dental arch relationships in patients treated in Warsaw with a one-stage repair were more favorable than in patients treated in Prague and Bratislava with a two-stage protocol and comparable to the best results obtained in the Eurocleft and Americleft studies.
Keywords: výsledek terapie; Cleft lip and palate; Goslon; retrospektivní studie; Slovakia; Slovenská republika; Cleft Lip; zubní oblouk; rozštěp patra; Poland; Česká republika; Cleft palate; Models, Dental; Czech Republic; Treatment Outcome; Slavs; lidé; Dental arch relationship; zubní modely; Humans; rozštěp rtu; Cleft Palate; Retrospective Studies; Dental Arch; Polsko